Book Review: Supply Chain’s Flexibility – A Real Options Approach - Bishwajit Banik Pathik (International Journal of Supply Chain Management, 2013)
This book contains of the investigation is about the process of decision making in supply chain management using a real options analysis framework. Specifically, the authors address issues regarding the optimal inventory level to hedge against demand uncertainties; the timing for equipment capacity implementation under market product mix complexity; the timing for workforce capacity reinforcement aiming market service requirements; and the decisions between integration and outsourcing in an uncertainty environment. Discrete and continuous time methodologies were used to identify the optimal value and timing of the options to adopt, when the demand is stochastic. Additionally, the effect of market requirements, such as product mix complexity and service level, were also taken into consideration. The demand is modeled under different stochastic processes; the impact of unexpected shocks is also explored, which enhances the generalization of the models to different business conditions. The applicability of the models enables the diversification and enrichment of the literature on the real options approach, within supply chain concept. Flexible inventory levels and the flexible capacity are supply chain features that can be used to deal with demand uncertainty.